A soluble Bacteroides by-product impairs phagocytic killing of Escherichia coli by neutrophils. - Rotstein, O D (1989)
The effect of Bacteroides culture filtrate on killing of Escherichia coli by neutrophils was examined as a potential mechanism for E. coli-Bacteroides microbial synergy. A low-molecular-weight heat-stable factor present in the 22-h culture filtrate of Bacteroides fragilis 9032 impaired neutrophil killing function. To determine whether short-chain fatty acids present in the filtrate could account for the inhibition, the fatty acid content of the culture filtrate was determined and sterile medium supplemented with measured concentrations of fatty acids was tested for its effect on neutrophil function. Succinic and acetic acids were measured in high concentrations, while lactic, formic, and fumaric acids were present in lower concentrations. Reconstituted media mimicked the inhibitory effect of B. fragilis filtrate on neutrophil killing capacity. In further support of the hypothesis that short-chain fatty acids were responsible for the inhibition, the filtrates of other Bacteroides strains were found to be inhibitory only after bacterial growth had entered the stationary phase, a period during which fatty acid production is maximized. Further studies investigating the mechanism of impaired neutrophil killing showed that B. fragilis 9032 culture filtrate inhibited both phagocytosis of [3H]thymidine-labeled E. coli by neutrophils and the intrinsic microbicidal functions of the neutrophil. Impairment of neutrophil superoxide production was mediated via the ability of short-chain fatty acids present in B. fragilis filtrate to reduce neutrophil cytoplasmic pH. These studies suggest that Bacteroides strains capable of reaching stationary phase in vivo may contribute to the pathogenesis of mixed infections by direct inhibition of neutrophil function.